Coronary angiography-related myocardial injury as detected by high-sensitivity cardiac troponin T assay - Abu Sharar, Haitham; Vafaie, Mehrshad; Kristen, Arnt; Volz, Hans Christian; Bekeredjian, Raffi; Katus, Hugo; Giannitsis, Evangelos (EuroIntervention, 2016)
The Official Journal of EuroPCR and the European Association of Percutaneous Cardiovascular Interventions (EAPCI)